2021
DOI: 10.1002/celc.202100496
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Reactionware for Synthetic Electrochemistry with Hydrogen Fluoride Reagents

Abstract: Electrochemical fluorination reactions of organic compounds frequently employ hydrogen fluoride reagents that are corrosive. The corrosive nature of these reagents necessitates either the construction or purchase of cells that are stable to hydrogen fluoride, which require high-cost materials, machining time and expertise. Herein, we offer an alternative solution using 3D printing, which is an inexpensive and rapid manufacturing technique. We have designed, printed and shared four different cell types in polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 72 publications
(73 reference statements)
1
10
0
Order By: Relevance
“…However, Lennox et al reported the electrochemical cells that has been 3D printed and it is a cost effective, facile technique, efficient to handle the harsh reaction conditions integral in the use of HF in organic reactions. [190] Similar work has been reported from Lennox et al in which alkene 55 undergoes difluorination to form alkane 56 by electrochemical oxidation using a mixture of pyridinium ploy(HF) in CH 2 Cl 2 ęhexafluoroisopropanol (HFIP) and Et 3 N.3HF with 4-iodotoluene as a mediator [191] (Scheme 26). During this conversion, a divided cell is used for oxidatively sensitive substrates while undivided cell is required for more oxidatively stable substrates.…”
Section: Electrochemical Fluorinationssupporting
confidence: 55%
See 1 more Smart Citation
“…However, Lennox et al reported the electrochemical cells that has been 3D printed and it is a cost effective, facile technique, efficient to handle the harsh reaction conditions integral in the use of HF in organic reactions. [190] Similar work has been reported from Lennox et al in which alkene 55 undergoes difluorination to form alkane 56 by electrochemical oxidation using a mixture of pyridinium ploy(HF) in CH 2 Cl 2 ęhexafluoroisopropanol (HFIP) and Et 3 N.3HF with 4-iodotoluene as a mediator [191] (Scheme 26). During this conversion, a divided cell is used for oxidatively sensitive substrates while undivided cell is required for more oxidatively stable substrates.…”
Section: Electrochemical Fluorinationssupporting
confidence: 55%
“…However, Lennox et al. reported the electrochemical cells that has been 3D printed and it is a cost effective, facile technique, efficient to handle the harsh reaction conditions integral in the use of HF in organic reactions [190] . Similar work has been reported from Lennox et al.…”
Section: Electrochemical Fluorinationsmentioning
confidence: 70%
“… 80 However, as most commercially available electrochemistry equipment is produced from glass, researchers have had to rely on highly expensive, custom-made HF-resistant reaction vessels for electrochemical reactions with HF. To address this problem, the Lennox team recently reported the use of 3D-printed, HF-resistant reaction vessels for electrochemistry 81 and showcased their effectiveness during a difluorination of olefins by pyridinium poly(HF) ( Scheme 8 ). The reaction vessels were made from cheap, 3D-printable polypropylene (PP) and during comparisons with other reaction vessel materials, the team reported a significant decrease in yield when using an electrochemical cell made from glass ( Scheme 8 ).…”
Section: C–f Bond Formationmentioning
confidence: 99%
“…The aim is to gain a better understanding of the influence of design parameters like electrode arrangement and surfacearea-to-volume ratio. Additionally, the application of increasingly considered 3D printing techniques [11,19,20] is extended to microscale reactors, which attracted the interest of electrochemical research in recent years [17,[21][22][23]. chanical tools and trained labor.…”
Section: Introductionmentioning
confidence: 99%